Probiotics bacteria and enteric infections : cytoprotection by probiotic bacteria - Koninkx, Jos F. J. G. [ (Joseph Frans Jan Gerard)] , 1944-; Malago, Joshua J. [ (Joshua Joseph)]; Marinsek-Logar, Romana , 1960- (Springer, 2011)
Every day many people suffer from intestinal diseases. These disorders can result from pathogens like bacteria, fungi, parasites and viruses, but the causes of non-infectious intestinal disorders and colorectal cancers remain to be elucidated. Disturbances to the normal gut flora (the microbiota) are central to the development of many, if not all, of these disorders. Disturbed gut microbiota is a prelude to public health issues like traveller's-, antibiotic- and Clostridium difficile-associated diarrhoea, irritable bowel syndrome, inflammatory bowel disease, and colorectal cancers